Impact of geometric factor in accumulation factor measurements of gamma rays (Baghdad Science Journal, 2005)
In this research a study process to calculate the factor accumulation of gamma rays for aluminum and exporters cobalt 60 Mika Atktron volts and actively radiation Vdrh 1.406 Mika Bq been studying the effect of the angle of reimbursement and the distance between the shield and detector In measurements factor accumulation Adhrt results in line with the theoretical results published